Drosophila insulin‐like peptide dilp1 increases lifespan and glucagon‐like Akh expression epistatic to dilp2. Issue 1 (3rd December 2018) - Post, Stephanie; Liao, Sifang; Yamamoto, Rochele; Veenstra, Jan A.; Nässel, Dick R.; Tatar, Marc
Abstract: Insulin/IGF signaling (IIS) regulates essential processes including development, metabolism, and aging. The Drosophila genome encodes eight insulin/IGF‐like peptide ( dilp ) paralogs, including tandem‐encoded dilp1 and dilp2 . Many reports show that longevity is increased by manipulations that decrease DILP2 levels. It has been shown that dilp1 is expressed primarily in pupal stages, but also during adult reproductive diapause. Here, we find that dilp1 is also highly expressed in adult dilp2 mutants under nondiapause conditions. The inverse expression of dilp1 and dilp2 suggests these genes interact to regulate aging. Here, we study dilp1 and dilp2 single and double mutants to describe epistatic and synergistic interactions affecting longevity, metabolism, and adipokinetic hormone (AKH), the functional homolog of glucagon. Mutants of dilp2 extend lifespan and increase Akh mRNA and protein in a dilp1 ‐dependent manner. Loss of dilp1 alone has no impact on these traits, whereas transgene expression of dilp1 increases lifespan in dilp1  −  dilp2 double mutants. On the other hand, dilp1 and dilp2 redundantly or synergistically interact to control circulating sugar, starvation resistance, and compensatory dilp5 expression. These interactions do not correlate with patterns for how dilp1 and dilp2 affect longevity and AKH. Thus, repression or loss of dilp2 slows aging because its depletion induces dilp1, which acts as a pro‐longevity factor. Likewise, dilp2 regulates Akh through epistatic interaction with dilp1 . Akh and glycogen affect aging in Caenorhabditis elegans and Drosophila . Our data suggest that dilp2 modulates lifespan in part by regulating Akh, and by repressing dilp1, which acts as a pro‐longevity insulin‐like peptide.